Robotic-assisted Hip And Knee Arthroplasty: A Bibliometric Analysis Using The Scopus Database - Ren Yi Kow; Rizal Abdul Rani; Mohamad Hilmi Mohaamd Nazarallah; Juzaily F.Leong; Muhammad Fathi Hayyun; Chooi Leng Low; Ahmad Hafiz Zulkifly; Nor Hamdan Mohamad Yahaya (CUREUS, 2024)
Indexed by WOS